Intra‐operative duplex ultrasound scanning in renal transplantation: protocol and service requirements - Linda Thebridge; Charles Fisher; Vikram Puttaswamy; Carol Pollock; Jillian Clarke (Journal of Medical Radiation Sciences)
Abstract Intra‐operative duplex ultrasound in renal transplantation was first described in 1998 and whilst reported in problematic cases, there are few reports of its routine use and no current published protocols. Since 2013, we have used intra‐operative ultrasound in all renal transplants. The formal protocol used since August 2020 is presented as a reference document for other transplant centres. A Canon Aplio 800 ultrasound system with an i22LH8 hockey‐stick transducer is used to image the renal cortex and major vessels, and an i8CX1 matrix transducer to image the graft during and after fascial closure. These transducers are fully sterilised with Sterrad and no sheathing of transducers is required. The transplant surgeon scans within the sterile field with the sonographer guiding imaging and adjusting machine settings. Ultrasound findings are discussed between team members including any requirement for interventions. Ultrasound is performed at three stages of the operation: Stage 1: after clamp release identifying issues of graft vascularity including otherwise unrecognised major vessel and anastomotic abnormalities. Stage 2: following ureteric implantation identifying compromised perfusion due to graft rotation or vessel kinking. Stage 3: after fascial closure identifying compromised perfusion due to external compression. Post‐operative scanning, including assessment of the collecting system and bladder, is performed routinely on days 1, 3, 7 and 30. The intervention is effective with no early graft losses or peri‐operative vascular thromboses. The requirements for service provision are significant including the availability of additional transducers, and sonographers with expertise in intra‐operative scanning able to attend after‐hours for extended periods.